The migraine postdrome. Issue 3 (June 2016) - Bose, Pyari; Goadsby, Peter J.
Abstract : Purpose of review: Migraine is a common, disabling neurological disorder that affects up to 12% of the world population. Its pathophysiology is incompletely described. Of the various phases of migraine, the migraine postdrome is the least studied and hence the least understood. Recent findings: Electronic diary studies show patients are left disabled with non-headache symptoms in the migraine postdrome. Hence, the importance of understanding the phase better and ensuring that more effective treatments become available in the future to cut down the morbidity associated with this phase. Summary: The disability related to migraine is not limited to the headache phase and pans out to include the postdrome phase. The migraine postdrome needs to be studied more as this may improve our overall understanding of migraine mechanisms and also treat the concurrent symptoms better.